Plautus, Rotrou, Molière: Amphitryon and the violence of reception. (17th October 2017) - Hiscock, Matthew
Abstract: A sample of the reception of the Amphitryon myth is used to suggest that engagements with it are prompted by, and express, self-conscious reflection on the practice and 'ethics' of reception. Analysis of the ensuing dialogue reveals important differences in approach, and the discussion as a whole aims to suggest the possible benefits of a non-chronological, though profoundly historical, perspective that attends to each of the texts considered in roughly equal measure, and for their mutual illumination. The gains, in this instance, are a reassessment of the passage on theatrical ambitus in the Prologue of Amphitruo ; a re-evaluation of Jean de Rotrou's Les Sosies, which is shown to anticipate Molière's reception; and an exploration of the violence implicit in Amphitryon that sets it apart from the other texts. The latter prompts a new explanation of Molière's decision to stage the myth: as an expression of, and response to, an aggressive model of reception embodied in the establishment of the Académie de France à Rome.